Evaluating the protective efficacy of a trivalent vaccine containing Akabane virus, Aino virus and Chuzan virus against Schmallenberg virus infection - Hechinger, Silke (BioMed Central, 2013)
Schmallenberg virus (SBV), an arthropod borne pathogen, spread rapidly throughout the majority of Europe since 2011. It can cause a febrile disease, milk drop, diarrhea, and fetal malformation in ruminants. SBV, a member of the Simbu serogroup within the genus Orthobunyavirus, is closely related to Akabane virus (AKAV) and Aino virus (AINOV) among others. In the present study, 4 Holstein-Friesian calves were immunized twice four weeks apart with a multivalent, inactivated vaccine against AKAV and AINOV. Another 4 calves were kept as unvaccinated controls. All animals were clinically, serologically and virologically examined before and after challenge infection with SBV. AKAV- and AINOV-specific neutralizing antibodies were detected one week before challenge infection, while SBV-specific antibodies were detectable only thereafter. SBV genome was detected in all vaccinated animals and 3 out of 4 controls in serum samples taken after challenge infection. In conclusion, the investigated vaccine was not able to prevent an SBV-infection. Thus, vaccines for other related Simbu serogroup viruses can not substitute SBV-specific vaccines as an instrument for disease control.